Charge Exchange Effects in Collisional Ionization Equilibrium of C,N, and O Ions - Kwang-Il Seon (Journal of Astronomy and Space Sciences, 2004)
The charge exchange (or transfer) due to collision with hydrogen has important effects on the physical characteristics of astrophysical plasma. In this paper, collisional ionization equilibrium in the temperature range of ˜ 1,000--80,000 K are investigated for C, N, and O ions including the effects of charge exchange. The calculated ionic abundance fractions are compared with those of previous works. The ionic abundance fractions calculated in the paper can be used in understanding the spectroscopic properties of warm interstellar medium. It is also found that the ratio between the degree of ionization of oxygen and that of hydrogen shows big difference with the previously well-known result for the environment where the collisional ionization is not important. This implies that investigations on the collisional ionization in the warm interstellar medium are required.